From Dual Energy X-Ray Absorptiometry ot Positron Emission Tomography: Diverse Imaging Approaches to Body Composition - Faradilla Novita Anggreini; Elysanti Dwi Martadiani; Dewa Gede Mahiswara Suadiatmika (GLOBAL HEALTH SCIENCE GROUP, 2025)
Accurate body composition assessment is crucial for diagnosing and managing health issues such as obesity, osteoporosis, and metabolic disorders. Diverse imaging approaches, including DXA, US, CT, MRI, and PET, each offer unique insights into body composition. By exploring these diverse imaging methods, clinicians and researchers can achieve a comprehensive understanding of body composition, leading to enhanced diagnostic accuracy and more personalized treatment strategies. Comprehensive understanding of various imaging techniques such as Dual Energy X-ray Absorptiometry (DXA), Ultrasonography (US), Computed Tomography (CT), Magnetic Resonance Imaging (MRI) and Positron Emission Tomography (PET) in body composition analysis. Body composition analysis utilizes several imaging techniques to provide a comprehensive assessment. DXA is used to measure bone mineral density and differentiate between fat and lean mass by analyzing how X-rays are absorbed at two different energy levels. US uses high-frequency sound waves to create real-time images of soft tissues, enabling the measurement of muscle thickness and fat layers. CT scans offer detailed cross-sectional images of fat and muscle distribution, while MRI produces high-resolution images of soft tissues without radiation. PET scans use radiotracers to monitor metabolic activity and detect functional changes in tissues.The exploration of diverse imaging approaches reveals the strengths and limitations of each method in body composition analysis. DXA is gaining popularity among clinicians for body composition analysis because it provides accurate measurements of lean and fat mass, similar to CT and MRI, but at a lower cost and with less invasiveness. Its widespread availability and precision in assessing both bone mineral density and soft tissue composition across the entire body or specific regions make DXA a valuable tool for managing osteoporosis and studying changes in body composition in various health conditions.